Mechanical characteristics of experimental multi-scale steel fiber reinforced polymer concrete and optimization by Taguchi methods. (27th December 2021) - Esmaeili, Jamshid; Andalibi, Keyvan; Gencel, Osman
Highlights: Mechanical characteristics of steel fiber reinforced polymer concrete were experimentally investigated. Taguchi method and analysis of variance were used to optimize mixture of polymer concrete. Three different polymer contents, two filler contents and three different steel fiber contents were used. It was observed that increasing percentage of polymer content from 10 to 15% improves mechanical properties. Abstract: Polymer Concrete (PC) has been widely used in reinforced concrete structures over the past few decades. Despite that, few studies have performed on its mechanical behavior. The present work investigates the PC mechanical behavior. Polymer concrete mixes were prepared and tested with three different polymer content (10%, 15% and 20%) and two filler contents (20% and 30%) and three different content of steel fiber (0.5%, 1% and 2%). In this study used the mix of cement and Micro-Silica as the filler. Afterward, Taguchi method and analysis of variance (ANOVA) were used to optimize the polymer concrete mix design based on the results of compressive strength, tensile strength and flexural strength in different percentages of polymer and fiber contents. Non-destructive ultrasonic pulse velocity test was also performed to estimate the porosity of the specimens. Scanning electron microscope (SEM) was used to analyze the interface between the aggregates and the polymer, the microstructure phase and the pores in the polymer concrete structure. Experimental results show that increasing the percentage of polymer content from 10 to 15% improves the mechanical properties of polymer concrete, while increasing this polymer content by up to 20% reduces the mechanical properties of the polymer composite. Based on non-destructive tests (NDT), it was found that increasing the content of cement and micro-silica reduces the porosity of the specimens. Moreover, as the content of steel fibers increases, the ductility and energy absorption of the specimens increase. At the end of this study, two functions were proposed to predict the mechanical properties of PC.